Risk assessment of digital library information security: a case study. Issue 3 (6th June 2016) - Han, Zhengbiao; Huang, Shuiqing; Li, Huan; Ren, Ni
Abstract : Purpose: This paper uses the GB/T20984-2007 multiplicative method to assess the information security risk of a typical digital library in compliance with the principle and thought of ISO 27000. The purpose of this paper is to testify the feasibility of this method and provide suggestions for improving information security of the digital library. Design/methodology/approach: This paper adopts convenience sampling to select respondents. The assessment of assets is through analyzing digital library-related business and function through a questionnaire which collects data to determine asset types and the importance of asset attributes. The five-point Likert scale questionnaire method is used to identify the threat possibility and its influence on the assets. The 12 respondents include directors and senior network technicians from the editorial department, comic library, children's library, counseling department and the learning promotion centre. Three different Guttman scale questionnaires, tool testing and on-site inspection are combined to identify and assess vulnerabilities. There were different Guttman scale questionnaires for management personnel, technical personnel and general librarian. In all, 15 management librarians, 7 technical librarians and 72 ordinary librarians answered the vulnerability questionnaire. On-site inspection was conducted on the basis of 11 control domains of ISO 27002. Vulnerabilities were scanned using remote security evaluation system NSFOCUS. The scanning covered ten IP sections and a total of 81 hosts. Findings: Overall, 2, 792 risk scores were obtained. Among them, 282 items (accounting for 10.1 per cent of the total) reached the high risk level; 2 (0.1 per cent) reached the very high risk level. High-risk items involved 26 threat types (accounting for 44.1 per cent of all threat types) and 13 vulnerability types (accounting for 22.1 per cent of all vulnerability types). The evaluation revealed that this digital library faces seven major hidden dangers in information security. The assessment results were well accepted by staff members of this digital library, which testified to the applicability of this method to a Chinese digital library. Research limitations/implications: This paper is only a case study of a typical Chinese digital library using a digital library information security assessment method. More case-based explorations are necessary to prove the feasibility of the assessing strategy proposed in this study. Originality/value: Based on the findings of recent literature, the authors found that very few researchers have made efforts to develop methods for calculating the indicators for digital library information security risk assessment. On the basis of ISO 27000 and other related information security standards, this case study proposed an operable method of digital library information security risk assessment and used it to assess a the information security of a typical Chinese digital library. This study can offer insights for formulating a digital library information security risk assessment scale.